Singularidade e universalidade em A interpretação dos sonhos, de Sigmund Freud - Mattos, André Santana (2013)
In The interpretation of dreams, Freud presents a rich material of dream analyses, which is articulated with the establishment of general theses about the dream, leading into the metapsychological formulations about the psychic apparatus carried out in the seventh and last chapter. With the purpose of investigating the relations between singularity and universality that are characterized in the book, we have distinguished, among these three epistemic planes, two moments where it is constituted, in which one of them, a relation between two of those planes. In the first moment, we have analyzed the relation that finds itself in the domain between one dream and all dreams, i.e., between the detailed analysis of a singular dream and the general theses about the dream. We have identified that in the articulation between these two terms Freud makes use of the profound analysis of singular cases, taken as exemplar cases that present more clearly a determinate general characteristic of dream, but he also extends himself in brief analyses of various dreams, dwelling on the plurality of experience that articulates itself to a general thesis. In a second moment we have analyzed the relations that are at stake when we take the dream as one psychic formation among others, establishing epistemic relations with the psychopathological formations and with the psychic apparatus, which should be responsible for all psychic formations. While Freud initially intends to base the explication of psychopathological formations in the explication of dream, this epistemic order is inverted, in so far as it is based on the psychology of neurosis that he is going to justify the universality of the presence of the infantile desire on dream. In the same way, while a first reading that tried to understand the schema of the psychic apparatus only based on the interpretation of dreams would find its limit, it is necessary to recognize that there is a reciprocal subordination between the interpretation and the metapsychological explanation, as asserted by Monzani.